Analysis of Taiwanese pre-service teachers' perceptions of and activity designs on school-based English camps for elementary school EFL learners. Issue 2 (14th March 2020) - Chien, Chin-Wen
ABSTRACT: This study focused on 22 Taiwanese pre-service teachers' perceptions of school-based English camps. Based on the data analysis of the final projects, the questionnaire, and participants' self-evaluation, peer-evaluation, and two in-service English teachers' evaluation, this study has the following major findings. First, participants' perceptions of school-based English camps improved in terms of resources, monitoring, activity and material designs, and selection of teaching methods. Secondly, participants' self-evaluation, peer-evaluation, and two in-service English teachers' evaluations of these ten projects varied in terms of goals, learners, and authenticity. From a practical perspective, this study proposed a model with six major factors in order to help pre-service teachers equip themselves with competency and skills in activity designs in school-based English camps for elementary school EFL learners.